2023
DOI: 10.1101/2023.05.24.542043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of RSV/SARS-CoV-2 co-infection on clinical disease and viral replication: insights from a BALB/c mouse model

Abstract: RSV and SARS-CoV-2 are prone to co-infection with other respiratory viruses. In this study, we use RSV/SARS-CoV-2 co-infection to evaluate changes to clinical disease and viral replication in vivo. To consider the severity of RSV infection, effect of sequential infection, and the impact of infection timing, mice were co-infected with varying doses and timing. Compared with a single infection of RSV or SARS-CoV-2, the co-infection of RSV/SARS-CoV-2 and the primary infection of RSV followed by SARS-CoV-2 results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a mathematical model that simulates the coinfections of some respiratory viruses like SARS-CoV-2, IAV, RSV, and RV, it was found that RSV had the most impact on the prevalence of SARS-CoV-2 when the two viruses co-circulated and that the coinfection of RSV with SARS-CoV-2 caused the largest suppression of SARS-CoV-2 infection [ 68 ]. This effect may be caused by the pre-infection of RSV, leading to the decreased replication of SARS-CoV-2 and clinical disease [ 69 ], which could mean that RSV provides some protection to SARS-CoV-2. This may be why, although there is an increase in hospital stays in patients with RSV and SARS-CoV-2 coinfection, there is no need for intensive care or mechanical ventilation [ 70 ].…”
Section: Pathology Disease Outcomes and Severitymentioning
confidence: 99%
“…In a mathematical model that simulates the coinfections of some respiratory viruses like SARS-CoV-2, IAV, RSV, and RV, it was found that RSV had the most impact on the prevalence of SARS-CoV-2 when the two viruses co-circulated and that the coinfection of RSV with SARS-CoV-2 caused the largest suppression of SARS-CoV-2 infection [ 68 ]. This effect may be caused by the pre-infection of RSV, leading to the decreased replication of SARS-CoV-2 and clinical disease [ 69 ], which could mean that RSV provides some protection to SARS-CoV-2. This may be why, although there is an increase in hospital stays in patients with RSV and SARS-CoV-2 coinfection, there is no need for intensive care or mechanical ventilation [ 70 ].…”
Section: Pathology Disease Outcomes and Severitymentioning
confidence: 99%